PPARγ Contributes to Immunity Induced by Cancer Cell Vaccines That Secrete GM-CSF - Goyal, Girija (Cancer Immunol Res, 2018)
Peroxisome proliferator activated receptor-γ (PPARγ) is a lipid-activated nuclear receptor that promotes immune tolerance through effects on macrophages, dendritic cells (DCs), and regulatory T cells (Tregs). Granulocyte-macrophage colony stimulating factor (GM-CSF) induces PPARγ expression in multiple myeloid cell types. GM-CSF contributes to both immune tolerance and protection, but the role of PPARγ in these pathways is poorly understood. Here, we reveal an unexpected stimulatory role for PPARγ in the generation of antitumor immunity with irradiated, GM-CSF–secreting tumor-cell vaccines (GVAX). Mice harboring a deletion of pparg in lysozyme M (LysM)-expressing myeloid cells (KO) showed a decreased ratio of CD8(+) T effectors to Tregs and impaired tumor rejection with GVAX. Diminished tumor protection was associated with altered DC responses and increased production of the Treg attracting chemokines CCL17 and CLL22. Correspondingly, the systemic administration of PPARγ agonists to vaccinated mice elevated the CD8(+) T effector to Treg ratio through effects on myeloid cells and intensified the antitumor activity of GVAX combined with cytotoxic T lymphocyte-associated antigen-4 antibody blockade. PPARγ agonists similarly attenuated Treg induction and decreased CCL17 and CCL22 levels in cultures of human peripheral blood mononuclear cells with GM-CSF–secreting tumor cells. Together, these results highlight a key role for myeloid cell PPARγ in GM-CSF–stimulated antitumor immunity and suggest that PPARγ agonists might be useful in cancer immunotherapy.